Romani Communities and Transformative Change: A New Social Europe - Cemlyn, Sarah; Daróczi, Anna; Ferkovics, Roland; Franz, Romeo; Galbraith, James K.; Kóczé, Angéla; Matache, Margareta; Rorke, Bernard; Rostas, Katalin; Ryder, Andrew; Ryder, Andrew; Setét, Jenő; et al. (Policy Press, 2020)
Available Open Access under CC-BY-NC-ND. Drawing on Roma community voices and expert research, this book provides a powerful tool to challenge conventional discourses and analyses on Romani identity, poverty and exclusion. Through the transformative vehicle of a 'Social Europe', this edited collection presents new concepts and strategies for framing social justice for Romani communities across Europe. The vast majority of Roma experience high levels of exclusion from the labour market and from social networks in society. This book maps out how the implementation of a new 'Social Europe' can offer innovative solutions to these intransigent dilemmas. This insightful and accessible text is vital reading for the policymaker, practitioner, academic and activist